Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1073/pnas.122352699
|View full text |Cite
|
Sign up to set email alerts
|

Selective impairment of reasoning about social exchange in a patient with bilateral limbic system damage

Abstract: Social exchange is a pervasive feature of human social life. Models in evolutionary biology predict that for social exchange to evolve in a species, individuals must be able to detect cheaters (nonreciprocators). Previous research suggests that humans have a cognitive mechanism specialized for detecting cheaters. Here we provide neurological evidence indicating that social exchange reasoning can be selectively impaired while reasoning about other domains is left intact. The patient, R.M., had extensive bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
131
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(142 citation statements)
references
References 40 publications
8
131
2
1
Order By: Relevance
“…This effect was also found for unfamiliar social contracts (Cosmides 1989), and has since been observed crossculturally (Sugiyama et al 2002). Furthermore the difference in cognitive processing of social contract over abstract tasks is further supported by the differences in performance of patients with brain damage (Stone et al 2002) as well as the finding that emotional processing predicted reasoning on social contract tasks but not abstract ones.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…This effect was also found for unfamiliar social contracts (Cosmides 1989), and has since been observed crossculturally (Sugiyama et al 2002). Furthermore the difference in cognitive processing of social contract over abstract tasks is further supported by the differences in performance of patients with brain damage (Stone et al 2002) as well as the finding that emotional processing predicted reasoning on social contract tasks but not abstract ones.…”
supporting
confidence: 56%
“…if you enter a building site, you must wear a hard-hat) (Fiddick et al 2000). Research has shown that reasoning about these rules activates different parts of the brain (Ermer et al 2006;Fiddick et al 2005;Stone et al 2002) and violations evoke different emotions (Fiddick 2004) than with social contract rules. Farrelly and Turnbull (2008) found, however, that individuals who violated both types of rules were remembered better than those that adhered to them.…”
mentioning
confidence: 99%
“…One significant piece of support for this "cheater detection module" hypothesis comes from a cognitive neuropsychological study [46]. In this study, a patient (R.M.)…”
Section: Cheater Detectionmentioning
confidence: 88%
“…These patients exhibit striking abnormalities in social judgment and behavior (Damasio 1994;Stone et al 2002;Beer et al 2006), and formal mathematical models of their performance during economic games point to a deficit in guilt-related signals (Krajbich et al 2009). However, the latter data alone cannot establish a selective role for the OFC in guilt feelings because brain lesions are seldom restricted to the OFC, and a variety of other behavioral abnormalities unrelated to guilt processing are typically present in these patients Rolls 2004).…”
Section: Discussionmentioning
confidence: 99%